Deep Insights into the Specific Evolution of Fungal Hybrid B Heme Peroxidases - Zámocký, Marcel; Musil, Miloš; Danchenko, Maksym; Ferianc, Peter; Chovanová, Katarína; Baráth, Peter; Poljovka, Andrej; Bednář, David (Biology, 2022)
In this study, we focus on a detailed bioinformatics analysis of hyBpox genes, mainly within the genomes of Sclerotiniaceae (Ascomycota, Leotiomycetes), which is a specifically evolved fungal family of necrotrophic host generalists and saprophytic or biotrophic host specialists. Members of the genus Sclerotium produce only sclerotia and no fruiting bodies or spores. Thus, their physiological role for peroxidases remains open. A representative species, S. cepivorum, is a dangerous plant pathogen causing white rot in Allium species, particularly in onions, leeks, and garlic. On a worldwide basis, the white rot caused by this soil-borne fungus is apparently the most serious threat to Allium-crop production. We have also found very similar peroxidase sequences in the related fungus S. sclerotiorum, although with minor yet important modifications in the architecture of its active centre. The presence of ScephyBpox1-specific mRNA was confirmed by transcriptomic analysis. The presence of Hybrid B peroxidase at the protein level as the sole extracellular peroxidase of this fungus was confirmed in the secretome of S. cepivorum through detailed proteomic analyses. This prompted us to systematically search for all available genes coding for Hybrid B heme peroxidases in the whole fungal family of Sclerotiniaceae. We present here a reconstruction of their molecular phylogeny and analyse the unique aspects of their conserved-sequence features and structural folds in corresponding ancestral sequences.
Keywords: hybrid B heme peroxidase; enzymatic antioxidant; ancestral sequence reconstruction; peroxidase–catalase superfamily; oxidative stress